1993
DOI: 10.2165/00003088-199325050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Slow-Acting Antirheumatic Drugs

Abstract: The pharmacokinetics of the slow acting antirheumatic drugs (SAARDs), hydroxychloroquine, chloroquine, penicillamine, the gold complexes and sulphasalazine, in humans have been studied. For all these drugs, both in controlled clinical trials and in empirical observations from rheumatological practice, delays of several months are reported before full clinical effects are achieved. Variability in response is also characteristic of these agents. Pharmacokinetic factors may partially explain these clinical observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 75 publications
(128 reference statements)
1
60
0
3
Order By: Relevance
“…The rationale for the dosing scheme of 72 h pretreatment prior to the first dose of DOX followed by continuous daily dosing with HCQ was based on the reported long halflife and time to reach steady-state in humans, and the lack of any corresponding pharmacokinetic data in dogs. [19][20][21] Four dose cohorts, ranging from 5 mg/kg/d up to 12.5 mg/kg/d, were evaluated. This study identified maximum tolerated doses of HCQ in combination with DOX of 12.5 mg/kg/d, and 25 mg/m 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for the dosing scheme of 72 h pretreatment prior to the first dose of DOX followed by continuous daily dosing with HCQ was based on the reported long halflife and time to reach steady-state in humans, and the lack of any corresponding pharmacokinetic data in dogs. [19][20][21] Four dose cohorts, ranging from 5 mg/kg/d up to 12.5 mg/kg/d, were evaluated. This study identified maximum tolerated doses of HCQ in combination with DOX of 12.5 mg/kg/d, and 25 mg/m 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Three HCQ metabolites have been identified, including N-desethylchloroquine, desethylhydroxychloroquine (DHCQ), and bidesethylchloroquine. 18,19 However, little is known about HCQ pharmacokinetics in dogs. HCQ has been used in canine discoid and cutaneous lupus erythematosus, similar to humans, at dosages of 5 to 10 mg/kg/d with some evidence of clinical efficacy, suggesting adequate blood and tissue concentrations for that specific indication.…”
Section: Introductionmentioning
confidence: 99%
“…These appear histologically as granulovacuolar cell mutations and ultrastructurally as lamellar inclusion bodies ("myeloid bodies") and as "curvilinear bodies" in cytoplasm (remnants of poorly digested membranes) 2,3 . Their pharmacokinetics are characterized by a long half-life and a high volume of distribution; they follow a multicompartment model with very slow distribution between plasma and tissue, leading to sustained organ sequestration and sometimes irreversible organ damage 4 .…”
Section: To the Editormentioning
confidence: 99%
“…The Journal of on May 7, 2018 -Published by www.jrheum.org Downloaded from lism of the substance 4 . Thus, the cardiac process may be asymptomatic for a long period.…”
Section: Rheumatologymentioning
confidence: 99%
“…SASP is variably absorbed, with estimates ranging from 10 to 30%, and undergoes extensive enterohepatic recycling. The metabolites of SASP have complex dispositional characteristics [10 ].…”
Section: Introductionmentioning
confidence: 99%